Alkilamida dari Buah Zanthoxyllum acanthopodium (Andaliman) - Musthapa, Iqbal; Nuraini, Vidia Afina; Gumilar, Gun Gun; Humairo, Ristvi (Jurnal Kartika Kimia, 2022)
An unsaturated alkylamide namely ZP-amida F, was isolated from the fruit of Zanthoxyllum acanthopodium. Discovery of this compound is first time in this plant. Determination of the structure using 1H-NMR and comparison with standard.